Validation of a model for predicting HIV pre-exposure prophylaxis uptake: a study protocol - Kileku, Elizabeth Nailantei; Sitienei, Joseph; Shisanya, Morris Senghor; Gitahi, Nyawira (Frontiers in Tropical Diseases, 2025)
IntroductionBy 2023, HIV will have claimed 40.4 million lives, posing a significant global public health risk, with youth at the highest risk of new infections. Pre-exposure prophylaxis (PrEP) reduces HIV transmission by 48.9% when combined with other prevention strategies. Despite increased PrEP programs in sub-Saharan Africa since 2015, uptake remains low due to various barriers. This study aims to validate a model identifying demographic, economic, social, behavioral, and structural factors influencing PrEP use in Turbo Sub-County, where uptake is among the lowest.MethodsThe study will employ a descriptive cross-sectional design using both quantitative and qualitative methods to gather data from youths aged 15–24 in Turbo Sub-County. Participants will be selected through multistage random sampling based on Wards and villages. Data will be collected via self-administered questionnaires, interviews, and Focus Group Discussions (FGDs). Analysis will include thematic methods for qualitative data and Structural Equation Modeling (SEM) will be used to validate the relationships predicting PrEP uptake at 95% confidence intervals and α < 0.05.ResultsThe study is expected to provide insights into factors influencing PrEP uptake among youths in Turbo Sub-County. The validated model will highlight key demographic, economic, and behavioral determinants, offering actionable data for enhancing HIV prevention strategies tailored to this population.DiscussionThe discussion will interpret the interplay of factors affecting PrEP uptake and compare findings with regional studies. It will emphasize community-specific barriers and enablers, informing targeted interventions and strategies to improve PrEP accessibility and acceptance.ConclusionsThe study aims to provide a validated framework for predicting PrEP uptake, guiding stakeholders in addressing barriers and strengthening interventions. The findings will support optimizing PrEP programs to reduce HIV transmission among at-risk youth.